1984
DOI: 10.1182/blood.v64.6.1207.1207
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of monoclonal proteins in the serum and urine of chronic lymphocytic leukemia patients

Abstract: Chronic lymphocytic leukemia (CLL) is generally considered a nonsecretory B cell immunoproliferative disorder. Conventional electrophoretic and immunoelectrophoretic methods have revealed serum monoclonal proteins in less than 10% of these patients. However, there is increasing experimental evidence from in vitro studies demonstrating that CLL cells may secrete immunoglobulins, particularly free light chains. We examined the serum and urine of 36 consecutive CLL patients for monoclonal proteins using sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Aberrant expression of j-MC in k leukaemias was seen in six cases. In the series of Deegan et al (1984), PP and leukaemic cells were always of the same LC isotype. Garand et al (2000) reported a single case of biclonal j + k PP in one j lymphoplasmacytoid leukaemia.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Aberrant expression of j-MC in k leukaemias was seen in six cases. In the series of Deegan et al (1984), PP and leukaemic cells were always of the same LC isotype. Garand et al (2000) reported a single case of biclonal j + k PP in one j lymphoplasmacytoid leukaemia.…”
Section: Discussionmentioning
confidence: 84%
“…Biclonal gammopathy seems to be more frequent in leukaemic B malignancies, comprising 13% of our PP cases, than in MGUS or myeloma, in which the frequency is classically reported as 1-3.5% (Van Hoof, Rombouts & Lepoutre, 1989;Osterborg, Hansson & Mellstedt, 1996). In the series of Deegan et al (1984), only one case of biclonality was found. In the series of secreting lymphoplasmacytoid leukaemias reported by Garand et al (2000), one biclonal j + k PP was found in one j leukaemia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It can be observed in many types of lymphoproliferative diseases classified as so-called nonsecretory lymphoid tumours. According to earlier reports, the incidence of component M in serum and/or urine NHL patients is about 10% (29,30).…”
Section: Discussionmentioning
confidence: 97%
“…However, the major drawback, limiting routine clinical use of these parameters, is the cost and complexity of technical procedures, underlying the necessity for further standardization. With this increased awareness, the focus of research has moved toward new simple prognostic markers allowing widespread clinical practice.Although monoclonal protein secretion is a typical feature of plasma cell dyscrasias, it can also be detected in other B cell malignancies including CLL (8,9). An abnormal free light chain ratio (FLCR), which was reported in 44% of patients with CLL, has proven to be predictive for progression of monoclonal gammopathy of uncertain significance, solitary plasmacytoma of bone, amyloidosis, multiple myeloma (MM), Waldenstro¨m's macroglobulinemia, and smoldering MM (9-16).…”
mentioning
confidence: 99%